The Framework Convention on Tobacco Control (FCTC) and implementation of tobacco control policies: Lessons learned from Indonesia and Thailand. Issue 4 (5th July 2022) - Moeis, Faizal Rahmanto; Nurhasana, Renny; Rahardi, Fandy; Novitasari, Danty; Shellasih, Ni Made; Inayati; Murwendah; Suriyawongpaisal, Paibul; Patanavanich, Roengrudee; Ratih, Suci Puspita
Abstract: The threat that the tobacco epidemic poses to public health underscores the importance of comprehensive tobacco‐related regulation. Despite aiming to reduce the prevalence of smoking, Indonesia still falls short of this goal. In contrast, within the same region, Thailand's achievement in controlling tobacco serves as a potential role model for Indonesia. To understand the issue, we conducted a literature review of the current regulatory framework as well as the implementation of the World Health Organization's Framework Convention on Tobacco Control (FCTC) and MPOWER framework in both countries. The review was supplemented with a Focus Group Discussion and an in‐depth interview with stakeholders in Thailand and Indonesia. This study finds that: (1) Indonesia currently lacks a strong tobacco control policy champion, whereas Thailand has several authorities that focus on the issue; (2) Thailand's tobacco product advertising and promotion and smoking bans are more restrictive compared to Indonesia's policies; and (3) Thailand's policies on tobacco pictorial health warnings, pharmacotherapy, and excise taxes are more extensive than Indonesia's. We recommend that Indonesia ratify the FCTC as the foundation of tobacco control policies while also strengthening and coordinating organizations working on tobacco control, encouraging subnational governments to introduce regulations, and enforce control, as well as improving excise policies to reduce the affordability of tobacco products. Key Points: Indonesia has yet to make significant progress in reducing smoking prevalence. Comprehensive tobacco control regulations are needed. Indonesia currently does not have a strong tobacco control policy, while Thailand has several authorities that focus on this issue. Indonesia needs to ratify the FCTC as a cornerstone of tobacco control policies and strengthen regulations on tobacco control.